Ethics in Research: An Overview for Novice Researchers - Smith, Stacia (Journal of Leadership, Accountability and Ethics, 2024)
Research studies involving human participants must be approved by the organization’s Institutional Review Board before data collection can begin. To a frustrated novice researcher who is struggling to obtain approval, this process can, at times, feel excessively rigorous. Inhumane and unethical experiments from the past have driven the evolution of research ethics regulations. Understanding the past and present requirements of ethical research helps novice and seasoned researchers alike to better appreciate the process. This paper will briefly introduce the history, landmark reports, current regulations, and ethical issues when conducting and publishing research that includes human subjects.